2001
DOI: 10.1002/bem.34
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of Canadian children's personal exposures to magnetic fields

Abstract: Study of the health effects of magnetic fields often depends on identifying determinants and hence indicators of personal exposure. This study identified determinants of children's exposure to magnetic fields and constructed a prediction model for them. For 632 children participating in a case-control study of childhood leukemia, we made direct measures of exposure over 48 h using a portable device, together with observations on candidate determinants. A child's age and sex, the proportion of time spent in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Regional differences in exposure have also been found among Canadian children (Deadman et al, 1999;Armstrong et al, 2001 ).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Regional differences in exposure have also been found among Canadian children (Deadman et al, 1999;Armstrong et al, 2001 ).…”
Section: Discussionmentioning
confidence: 88%
“…Our results suggest that factors intrinsic to the home influence childhood magnetic field exposures. Armstrong et al (2001 ) found the type of residence (e.g., single family home versus apartment ) to be a strong predictor of childhood exposure. Kavet et al (1999 ), focusing on homes located away from power lines, found that the presence of ground currents, the number of service drops on the same transformer serving the home, and increasing age of the home predicted higher residential magnetic fields.…”
Section: Discussionmentioning
confidence: 95%
“…Rankin et al (2002) reported a Spearman correlation of 0.74 between point-in-time MF measurements and personal exposures, but the personal exposure measurement was limited to exposure in the home. Studies on the correlation of spot measurements with total 24 h personal exposure have shown correlations from 0.37 to 0.77 for timeweighted average exposure (Armstrong et al, 2001;Eskelinen et al, 2002) and from 0.41 to 0.74 for threshold-type exposure metrics (Eskelinen et al, 2002). It is of interest that, in the present data, the correlations with total 24 h exposure are not generally lower than those with the 12 h spent at home.…”
Section: Resultsmentioning
confidence: 40%
“…To elucidate the mechanisms underlying the acceleration of cell damage (Armstrong et al 2001;Chun et al 1996), in the present study, the earlier step of cell damage on the cellular membrane integrity, mitochondrial features, appearance of apoptotic bodies, nucleus condensation, and lipid droplet accumulation is investigated with EM and TUNEL assay. Each of these end points showed a parallel correlation with apoptosis when the animals exposed to EMF for long time.…”
Section: Emf-induced Ultrastractural Changes and Apoptosis In Uterus mentioning
confidence: 99%